“Sharing the Halo”: Social and Professional Tensions in the Work of World War I Canadian Volunteer Nurses - Quiney, Linda (Journal of the Canadian Historical Association / Revue de la Société historique du Canada, 1998)
AbstractThe experience of some 500 Canadian and Newfoundland women who served overseas as Voluntary Aid Detachment (VAD) nurses during the Great War has been eclipsed by the British record. Sent as auxiliary assistants to trained nurses in the military hospitals, Canadian VADs confronted a complex mix of emotional, physical, and intellectual challenges, including their “colonial” status. As casually trained, inexperienced amateurs in an unfamiliar, highly structured hospital culture, they were often resented by the overworked and undervalued trained nurses, whose struggle for professional recognition was necessarily abandoned during the crisis of war. The frequently intimate physical needs of critically ill soldiers also demanded a rationalisation of the VAD's role as “nurse” within a maternalist framework that eased social tensions for both VAD and patient. As volunteers assisting paid practitioners, the Canadian VAD experience offers new insights into a critical era of women's developing professional identities.